2000
DOI: 10.1159/000047601
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Disease and the Risk of Ischaemic Stroke and Coronary Vascular Events

Abstract: Information on the presence and extent of carotid arterial wall disease has significant prognostic value. Carotid artery stiffness, intima-media thickness, and early plaque formation are potentially useful predictors of the risk of both ischaemic stroke and coronary heart disease in asymptomatic populations. Early carotid arterial wall disease is also a useful predictor of coronary artery disease on angiography and subsequent coronary vascular events in populations at risk of coronary heart disease. More advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 73 publications
(139 reference statements)
2
37
0
2
Order By: Relevance
“…Rupture of atherosclerotic plaques is crucial in the pathogenesis of acute coronary syndromes and strokes [20,21]. Interactions, within the ICA stenosing plaque, between connective tissue and the cells embedded into the fibrous cap overlying the inner core appear to determine the history of the ICA stenosis: plaque rupture or ulceration, intraplaque haemorrhage and luminal thrombosis are recognized causes of stroke [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rupture of atherosclerotic plaques is crucial in the pathogenesis of acute coronary syndromes and strokes [20,21]. Interactions, within the ICA stenosing plaque, between connective tissue and the cells embedded into the fibrous cap overlying the inner core appear to determine the history of the ICA stenosis: plaque rupture or ulceration, intraplaque haemorrhage and luminal thrombosis are recognized causes of stroke [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Interactions, within the ICA stenosing plaque, between connective tissue and the cells embedded into the fibrous cap overlying the inner core appear to determine the history of the ICA stenosis: plaque rupture or ulceration, intraplaque haemorrhage and luminal thrombosis are recognized causes of stroke [20,21]. Specific markers to identify in vivo ruptured plaques, or plaques prone to rupture, are not available.…”
Section: Introductionmentioning
confidence: 99%
“…With an aging global population, this is expected to continue and the burden on healthcare systems from cardiovascular disease is expected to rise. Vascular disease in one arterial territory predicts the presence of disease in other territories (Rothwell, 2000). The risk of a myocardial infarction or death increases significantly after a transient ischemic attack or stroke (Touze et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As for CIMT, the presence of atherosclerotic plaque in the carotid artery has consistently been associated with cardiovascular risk factors and with prevalent and incident vascular events [4][5][6][7][8][9][10][11][12][13][14][15] . Moreover, measurement of changes in plaque volume may be of value in assessing changes in atherosclerotic burden over time, as some studies have found a stronger association with vascular events for plaques than for CIMT 4,5,7,11,13) .…”
Section: Introductionmentioning
confidence: 99%